ANALISIS KUAT TEKAN,KUAT TARIK,DAN KUAT LENTUR BETON MENGGUNAKAN BAHAN TAMBAH SIKA VISCOCRETE-10 DAN FLY ASH( TINJAUAN ANALISIS PADA UMUR DELAPAN JAM SAMPAI DENGAN DUA PULUH EMPAT JAM) - TRAPSILO, FAMBAYUNG SETIOKO; , Ir. H. Suhendro Trinugroho, M.T; , Ir. H. Aliem Sudjatmiko, M.T (2015)
Concrete is the most widely used material on construction development today, both in buildings, bridges, dams, and other construction. The various development of implementation methods and materials used created various types of concrete and methods of implementation, one of them is the Quick Method of Hardened Concrete. This study was conducted to analyze the power / strength of concrete in effort to improve the quality and durability of concrete by the minimum age hardening of concrete, and by the replacement of sand with dust / stone dust and using addition material in the form of Sika Viscocrete-10 0.1% and fly ash 12.5 %, fas 0.35 and f'cr 20 MPa, the maximum strength of concrete is expected to be achieved only in a time between 8 to 24 hours. The overview of analysis in this study is the compressive strength and tensile concrete cylinder with diameter of 15 cm and height of 30 cm and flexural strength of concrete beams with length of 50 cm, 15 cm high and 15cm wide. Concrete mix design method using the method of SNI 03-2834-2000. After testing and research, the results obtained in concrete life of 8 - 24 hours, with additional sika viscocrete -10 and fly ash added into concrete increase its compressive strength of 23% -29% tensile strength of 24% -30% and a flexural strength of 24 % -33% of normal concrete. Keywords: concrete, dust, fly ash, sika viscocrete-10, compressive strength, tensile strength, flexural strength.